Atmosphere‐Snow Exchange Explains Surface Snow Isotope Variability. Issue 20 (18th October 2022) - Wahl, S.; Steen‐Larsen, H. C.; Hughes, A. G.; Dietrich, L. J.; Zuhr, A.; Behrens, M.; Faber, A.‐K.; Hörhold, M.
Abstract: The climate signal imprinted in the snow isotopic composition allows to infer past climate variability from ice core stable water isotope records. The concurrent evolution of vapor and surface snow isotopic composition between precipitation events indicates that post‐depositional atmosphere‐snow humidity exchange influences the snow and hence the ice core isotope signal. To date, however, this is not accounted for in paeleoclimate reconstructions from isotope records. Here we show that vapor‐snow exchange explains 36% of the summertime day‐to‐day δ 18 O variability of the surface snow between precipitation events, and 53% of the δD variability. Through observations from the Greenland Ice Sheet and accompanying modeling we demonstrate that vapor‐snow exchange introduces a warm bias on the summertime snow isotope value relevant for ice core records. In case of long‐term variability in atmosphere‐snow exchange the relevance for the ice core signal is also variable and thus paleoclimate reconstructions from isotope records should be revisited. Plain Language Summary: Ice core water isotope records are valuable climate proxies containing information about past climate. Climate reconstructions from ice cores have been based on the interpretation of the water isotope records as precipitation signal. Here we show that the humidity exchange between atmosphere and snow influences the surface snow isotopic composition in‐between precipitation events in summer. Thus, it is not the precipitation signal alone that defines the summer snow isotope signal but a combination of precipitation and post‐depositional atmospheric vapor‐snow exchange. This suggests, that climate reconstructions from ice core isotope records should account for post‐depositional processes in the interpretation of the water isotope signal, specifically when interpreting summer isotope signals. Key Points: Atmosphere‐snow exchange of water vapor is a key process for the signal formation of the snow isotopic composition Taking into account isotopic fractionation during sublimation we explain a significant share of the observed day‐to‐day isotope variability Atmosphere‐snow exchange introduces a warm‐bias in the net summer snow isotope signal that is not accounted for in ice core interpretations